Atlas Materia: Fieldwork Experience in the Material City - Guitart, Miguel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Today, architecture is primarily consumed through interfaces like Instagram, on-line journals, websites, video games and print publications. This is in part due to the fixed geographical position of architecture. Images allow architecture to be distributed to a broader audience. However, images also represent a problematic disembodiment of the built environment. The complicated relationship between architecture and its image is explored in the first section of this paper, Mnemosyne Field through an interrogation of Aby Warburg’s Mnemosyne Atlas. The second section of this paper, Atlas Materia investigates material qualities as conveyors of architectural identity through fieldwork. The material adjacencies and observational imperfections of fieldwork result in an equivocal architectural experience that takes place at the intersection of a city’s physical qualities and the phenomenological response they produce. This paper describes the pedagogical outcome of sensorial mapping strategies that provided a visual and tactile representation of the city of Buffalo, New York. Based on the experience of material properties, the ultimate objective of Atlas Materia is to help establish a link between phenomenology of perception and urban spaces through a material-centered strategy.